IN-VITRO EVALUATION AND MOLECULAR DOCKING CALCULATION OF TRICYCLIC PHTHALIMIDE QUINOXALINE ANALOGUES AS NOVEL INHIBITORS OF HIV-1 INTEGRASE USING GLIDE AND GOLD (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
As quinoxaline analogues have been computationally shown to be competent with other commercial antiviral drugs in terms of size and efficacy, their lack of utility is exemplified in the case of HIV integrase. The ability of molecular docking methods to locate selective inhibitors reinforces our view of structure-based drug discovery as a valuable strategy, not only for identifying lead compounds, but also for addressing receptor specificity. This study focuses on series of ligands that are screened for a successful candidate drug using rational drug design. In the present work, we proposed and evaluated the interaction of quinoxaline analogues along with HIV integrase (1QS4) as target by using the docking program GOLD and GLIDE. To study the molecular basis of interaction and binding affinity of quinoxaline analogues, these compounds were docked into active site of receptor using GLIDE. The best 10 compounds were screened out using high throughput virtual screening. These 10 compounds were further subjected to Induced Fit Docking. Based on overall studies, we can conclude that quinoxaline compounds were found to be more potent inhibitors based on glide score, glide energy and interaction with residues in the active site of the HIV integrase (1QS4). In future, these ten compounds (CHEMBL35109, CHEMBL369834, CHEMBL177311, CHEMBL177547, CHEMBL177515, CHEMBL177405, CHEMBL177705, CHEMBL174851, CHEMBL367104, CHEMBL369841 and CHEMBL424782) can be considered as effective candidates for the second generation drug discovery.